KESIAPSIAGAAN PETUGAS KESEHATAN PUSKESMAS DALAM MANAJEMEN BENCANA DI WILAYAH KERJAPUSKESMAS SILIH NARA KABUPATEN ACEH TENGAH - Adisah, Adisah; Silitonga, Evawani Martalena; Manurung, Jasmen; Hidayat, Wisnu; Wandra, Toni (Universitas Pahlawan, 2022)
Â Â Disaster management is a very important factor to reduce the impact of disaster events. This study aims to determine the preparedness of health workers in disaster management based on the characteristics, knowledge, attitudes and practices/previous experiences of health workers in disaster management. This type of research is a quantitative research with a cross sectional approach. The study was conducted in the Working Area of the Silih Nara Health Center, Central Aceh Regency in August 2021 with a population of 85 health workers and all of them were used as samples (total sampling). Data analysis used univariate, bivariate and multivariate analysis. The results of data analysis show that there is a relationship between age and knowledge and attitudes, while based on previous practice/experience there is no relationship; there is no relationship between gender and previous knowledge, attitude and practice/experience; there is a relationship between education and previous knowledge, attitudes and practices/experience; there is a long-standing relationship with knowledge but no long-standing relationship with previous attitudes and practices/experiences; there is a relationship between involvement in disaster response with previous knowledge, attitudes and practices/experiences; there is a relationship between disaster management training and previous attitudes and practices/experience, while disaster management training has no relationship with knowledge; There is a relationship between being included in the Rapid Action Team (TGC) with previous knowledge, attitudes and practices/experiences based on the preparedness of health workers in disaster management in the Work Area of the Silih Nara Health Center, Central Aceh Regency. The variable of disaster management training is the most dominant variable in the preparedness of health workers in disaster management in the Work Area of the Silih Nara Health Center, Central Aceh Regency.